2019
DOI: 10.1017/aog.2018.28
|View full text |Cite
|
Sign up to set email alerts
|

Calving controlled by melt-under-cutting: detailed calving styles revealed through time-lapse observations

Abstract: We present a highly detailed study of calving dynamics at Tunabreen, a tidewater glacier in Svalbard. A time-lapse camera was trained on the terminus and programmed to capture images every 3 seconds over a 28-hour period in August 2015, producing a highly detailed record of 34 117 images from which 358 individual calving events were distinguished. Calving activity is characterised by frequent events (12.8 events h−1) that are small relative to the spectrum of calving events observed, demonstrating the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
108
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(121 citation statements)
references
References 51 publications
10
108
3
Order By: Relevance
“…Although immediate calving responses to the 2015 lake drainage were confined to discrete ice-falls along the thermo-erosional notch, the subsequent topple events under ice-free lake conditions are indicative of increased stress gradients at the calving front promoting the outward toppling of unstable flakes and pillars of ice in response to debuttressing. Similarly, How et al (2019) observed that calving termini are highly sensitive to variations in backstress, with even relatively small reductions, such as those associated with the falling limb of an ocean tide, observed to increase calving frequency. The recurrence of waterline events within 24 hr of both the 2014 and 2015 lake drainages implies rapid reestablishment of melt-undercutting as the dominant driver of calving at Russell Glacier IDL.…”
Section: Effects Of Sudden Lake Drainage On Calving Dynamicsmentioning
confidence: 88%
See 1 more Smart Citation
“…Although immediate calving responses to the 2015 lake drainage were confined to discrete ice-falls along the thermo-erosional notch, the subsequent topple events under ice-free lake conditions are indicative of increased stress gradients at the calving front promoting the outward toppling of unstable flakes and pillars of ice in response to debuttressing. Similarly, How et al (2019) observed that calving termini are highly sensitive to variations in backstress, with even relatively small reductions, such as those associated with the falling limb of an ocean tide, observed to increase calving frequency. The recurrence of waterline events within 24 hr of both the 2014 and 2015 lake drainages implies rapid reestablishment of melt-undercutting as the dominant driver of calving at Russell Glacier IDL.…”
Section: Effects Of Sudden Lake Drainage On Calving Dynamicsmentioning
confidence: 88%
“…termini (e.g., Chapuis & Tetzlaff, 2014;How et al, 2019;Medrzycka et al, 2016), whereby relatively low-magnitude falls are the most prevalent calving mechanism, but mass loss is dominated by a small number of high-magnitude events.…”
Section: Calving Processesmentioning
confidence: 99%
“…Certainly, the presence of sills is known to modify fjord water properties substantially by blocking access of dense waters to the calving front (Gladish et al, 2015), but this extrapolation remains a simplification due to vertical mixing within fjords (e.g. Inall et al, 2014) and because periodic dense inflows over sills have been observed in Greenland (Mortensen et al, 2011). Therefore, both the retreat and submarine melt implementations would be improved with methods to quantify water mass transformation between the shelf and calving fronts.…”
Section: Missing Processes and Priorities For Future Improvementmentioning
confidence: 99%
“…For the time period of our experiment between 24 August and 2 September, the approach of Köhler et al (2016) yields an ice loss of about 18•10 6 m 3 . Since about two-thirds of the grounded vertical terminus area of Kronebreen are submarine (Lindbäck et al, 2018) and assuming that submarine ice loss occurs mainly through melting as suggested by our visual calving observations at Kronebreen and How et al (2019), the corresponding dynamic ice loss would be 6•10 6 m 3 which is just slightly above the values estimated from the KRBN and KRBS records in this study, i.e., the contribution of calving to frontal ablation would be 18-30% (Table 1). For the entire year of 2016, the approach of Köhler et al (2016) yields an ice loss of about 640±80•10 6 m 3 .…”
mentioning
confidence: 75%
“…CC BY 4.0 License. observations at other glaciers in Svalbard (How et al, 2019). In addition, an autonomous calving event detector is implemented to compare the time series of seismicity and directly observed calving (see Fig.…”
mentioning
confidence: 99%